Lingual Retainer Application Using Indirect Bonding Technique: A Technical Note - Genta Agani Sabah; Yağmur Lena Sezici; Enver Yetkiner (Mashhad University of Medical Sciences, 2022)
Introduction: Fixed retainers are the most commonly used method of retention after orthodontic treatment. Accurate and passive adaptation of the fixed retainer wire to the anterior teeth, in addition to moisture control during the bonding procedure, are of utmost importance. Therefore, indirect bonding techniques of fixed retainers have been recently introduced to overcome the disadvantages of direct bonding methods, such as moisture contamination and changes in the wire position during intraoral bonding. Another benefit of indirect bonding methods is less dedicated chair time for bonding fixed retainers. A modified technique is used for the construction of the silicone tray in this technical note of indirect bonding of lingual retainers.